Glucose-Lowering and the Risk of Cardiovascular Events With Antidiabetic Therapies: A Systematic Review and Additive-Effects Network Meta-Analysis - Carvalho, Luiz Sergio Fernandes de; Nogueira, Ana Claudia Cavalcante; Bonilha, Isabella; Luchiari, Beatriz; Benchimol, Alexander; Couri, Carlos Eduardo Barra; Borges, Jairo Lins; Barreto, Joaquim; Sposito, Andrei C. (Frontiers in Cardiovascular Medicine, 2022)
Aim To assess the impact of the HbA1c levels achieved with antidiabetic therapies (ADTs) on the risk of MACE. Methods A systematic search was performed in PubMed, Cochrane, and ClinicalTrials. gov for RCTs published up to March 2022 reporting the occurrence of MACE and all-cause mortality in individuals with T2DM treated with all marketed ADTs, including a sample size ≥100 individuals in each study arm and follow-up ≥24 weeks. A systematic review and additive-effects network meta-analysis with random effects and a multivariate meta-regression were utilized to assess the impact of achieved HbA1c on incident MACE. Results We included 126 RCTs with 143 treatment arms, 270,874 individuals, and 740,295 individuals-years who were randomized to an active treatment vs. control group. Among all ADTs, only therapy with SGLT2i, GLP1-RA, or pioglitazone similarly reduced the risk of MACE compared to placebo. The achievement of HbA1c ≤ 7.0% in RCTs with the 3 drug classes in the active arm was associated with an adjusted HR of 0.91 (95% CI 0.80, 0.97; p = 0.017) compared with HbA1c>7.0%, without affecting all-cause mortality. These results, however, were not maintained among all ADTs. Conclusions Achieving lower glucose levels with SGLT2i, GLP1-RA, or pioglitazone is linearly associated with a reduced risk of MACEs, without affecting all-cause mortality. Systematic Review Registration www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020213127, identifier: CRD42020213127.